PROBLEMS FACED BY EFL STUDENTS IN CARRYING OUT ONLINE PRESENTATION - Abubakar, Multazam; Fadillah, Rezky Asryatul; Nurpahmi, Sitti (English Language Teaching for EFL Learners Journal, 2022)
This study aims at finding out the problems and the factors causing the problems faced by the students of English Education Department in carrying out online presentations. The subject of this research were 6 students of English Education Department of UIN Alauddin Makassar who enrolled in Speaking for Academic Purpose course. The samples were selected purposively. This study uses qualitative descriptive and the data were taken from observations through the Google Meet application and interview. The findings showed that the students had linguistic and non-linguistic problems. The linguistic problems faced are lack of vocabulary, lack of grammar and poor pronunciation; while, the non-linguistic problems are fear of making mistakes, feelings of shame, lack of self-confidence, network problems and disturbances that occur around students’ homes.